2022
DOI: 10.1101/2022.08.15.504010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host and viral determinants of airborne transmission of SARS-CoV-2 in the Syrian hamster

Abstract: Airborne transmission is one of the major routes contributing to the spread of SARS-CoV-2. Successful aerosol transmission occurs when people release respiratory particles carrying infectious virus in the fine aerosol size range. It remains poorly understood how infection influences the physiological host factors that are integral to this process. Here we assessed the changes in breathing, exhaled droplets, and released virus early after infection with the Alpha and Delta variants in the Syrian hamster. Infec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Delta and Omicron variants were the most persistent during the pandemic. Port 45 has shown that golden hamsters inoculated with SARS‐CoV‐2 virus maintain a high level of viral transmission during the first 5 days of infection followed by a drop. Throat swabs were harvested and detected on days 2 and 4 postchallenge in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Delta and Omicron variants were the most persistent during the pandemic. Port 45 has shown that golden hamsters inoculated with SARS‐CoV‐2 virus maintain a high level of viral transmission during the first 5 days of infection followed by a drop. Throat swabs were harvested and detected on days 2 and 4 postchallenge in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SARS-CoV-2 transmission could occur at this distance between Syrian hamsters even within 1 h at a 2:2 ratio (two infected index and two recipient naïve hamsters). Investigators were also able to demonstrate with this system that airborne transmission dynamics and aerosol characteristics (viral load and particle size) were different between SARS-CoV-2 variants and male and female hamsters ( 10 , 18 ). Dowall et al used a set of three cages, each linked through a 130-mm-diameter connector, and reported SARS-CoV-2 RNA shedding in donor and recipient animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although these features establish our model as a unique and workable tool for studying SARS-CoV-2 transmission, other animal models, such as hamsters and ferrets, have certain advantages over the limitations of our system. For instance, our transmission model is based on a mixture of droplet and contact transmission [70]; therefore, any variant-intrinsic differences that can be affected by airborne droplet formation and virion stability cannot be studied in our system, as opposed to the hamster model [49, 120]. An additional limitation of our model is the non-physiological expression of hACE2.…”
Section: Discussionmentioning
confidence: 99%